OC-106 Activation of the bile acid receptor, farnesoid-x receptor, may reduce ileal inflammatory cytokine expression in an animal model of diet-induced obesity. (22nd June 2015) - Speight, RA; Whitehead, A; Patman, G; Mansfield, JC; Reeves, H; Kirby, JA
Abstract : Introduction: A high fat (HF)/high sugar (HS), Western diet has been implicated in the pathogenesis of IBD. 1 The BA receptor, farnesoid-x receptor (FXR), is central to the crosstalk between the host and its microbiota. 2 FXR has an immuno-modulatory role in the GI tract. 3, 4 We hypothesised that disruption to BA signalling, induced by a HF/HS diet associated dysbiosis, is a mechanism linking diet to the development of IBD. The aim of this study was to investigate the effect of HF/HS feeding and FXR agonism on ileal inflammation in a mouse model of obesity. Method: Animal husbandry was performed under licence from the Home Office (as per ASPA 1986). C3H/He mice (n = 44) were fed standard chow or HF/HS chow (trans-fats, with fructose corn syrup). At 24 weeks, feed was supplemented with an FXR agonist (5 mg/kg or 1 mg/kg of feed) or control. At 42 weeks, body weight and visceral adipose tissue (VAT) weight was recorded and the ileum was dissected. The expression of TNFα, IFNγ and IL-6 was measured by RT-PCR (ΔΔCt method). FXR and its downstream targets, SHP and IBABP, were measured to assay for FXR activity. T- tests, regression analysis and Pearson correlation were calculated using Prism version 6.0e. P values were 2-tailed, a P value of <0.05 was considered significant. Results: Mice fed a HF/HS diet were significantly heavier, with more VAT than mice on the control diet (mean weight of 49.9 g versus mean weight of 41.6 g, p < 0.01). There was a positive correlation between the amount of VAT and the ileal expression of TNFα and IFNγ (y = 1.32*X p = 0.05, y = 1.24*X p = 0.02 respectively). The FXR agonist significantly increased the expression of IBABP (fold increase of 2.0, p = 0.01). In HF/HS fed mice, supplementation with 1 mg/kg FXR agonist attenuated the increase in ileal expression of all cytokines assayed, although the observed trend failed to reach significance. Conclusion: Animals fed a western lifestyle diet express more ileal inflammatory cytokine. There is a trend to suggest that supplementation with an FXR agonist reduces diet induced cytokine expression. By mediating dietary risk, FXR may be a potential therapeutic target in IBD, particularly to reduce relapses in patients with known disease. Disclosure of interest: None Declared. References: Ananthakrishnan AN. Gastroenterol Hepatol. 2013;9(6) Swann JR, Want EJ, et al . PNAS 2011;108(1) Vavassori P, Mencarelli A, et al . J Immunol. 2009;183 Gadaleta RM, van Erpecum KJ, et al . Gut 2011;60